(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article explores the significance of integrating environmental education into the teaching of biological sciences. It highlights the importance of this approach in fostering a comprehensive understanding of ecological systems, promoting environmental literacy, and cultivating a sense of responsibility towards the environment among students. The article discusses two primary ideas: the incorporation of real-world examples and practical experiences into the curriculum, and the use of interactive teaching methods to enhance student engagement. It further expands on the benefits of environmental education in promoting a sustainable future, emphasizing the role of educators in prioritizing the integration of environmental education in their teaching practices.